Invasive Fish Reshape Biodiversity Patterns in China's Freshwater Lakes - Zhice Liang; Rodolphe Elie Gozlan; Jiashou Liu; Donald Jackson; Chuanbo Guo (Global Change Biology, 2025)
Globalization has dramatically accelerated the spread of non‐native species, intensifying threats to freshwater ecosystems. While China ranks among the most heavily invaded countries, the role of non‐native species as key drivers of biodiversity changes is often overlooked in research on anthropogenic impacts. This oversight hampers the development of effective conservation and management strategies by limiting a full understanding of what shapes biodiversity patterns. To bridge this gap, an extensive dataset from 131 lakes across China was compiled and analyzed using a novel composite diversity index that integrates species richness with functional and phylogenetic uniqueness, allowing for a more precise identification of fish multidimensional diversity hotspots. Additionally, gradient forest models were employed to elucidate the impacts of non‐native species, geography, climate, and physicochemical factors on these patterns. Our findings revealed significant taxonomic and functional homogenization in non‐native hotspots within the overall fish community, coupled with phylogenetic diversification. Notably, non‐native fish diversity emerged as the primary factor shaping overall and native fish multidimensional diversity patterns. While the establishment of non‐native species may provide an immediate enhancement to overall diversity, it often leads to the extirpation/extinction of native species, ultimately resulting in biodiversity loss at local and potentially the regional scale. This study highlights the importance of examining multiple dimensions to characterize the intricate dynamics between native and non‐native species, which is essential for understanding their true impact on biodiversity and for achieving global conservation goals.